2015
DOI: 10.1111/ocr.12070
|View full text |Cite
|
Sign up to set email alerts
|

3D superimposition and understanding temporomandibular joint arthritis

Abstract: Objectives To investigate the 3D morphological variations in 169 Temporomandibular Joint (TMJ) condyles, using novel imaging statistical modeling approaches. Setting and Sample Population The Department of Orthodontics and Pediatric Dentistry at the University of Michigan. Cone beam CT scans were acquired from 69 subjects with long-term TMJ osteoarthritis (OA, mean age 39.1 ± 15.7 years), 15 subjects at initial consult diagnosis of OA (mean age 44.9 ± 14.8 years) and 7 healthy controls (mean age 43 ± 12.4 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
0
10
0
3
Order By: Relevance
“…Bone changes of the TMJ condyle were qualitatively measured based on visual evaluation of 9 sections of the TMJ condyle. Cevidanes et al 23,24 suggested a 3 dimensional quantification condylar resorption model technique and Ok et al 11 used superimposition with 6-imaginary sections to assess the longitudinal bone change in TMJ OA. Although both methods are suitable to assess TMJ OA, the method applied in this study was sufficient to highlight the importance of cortical bone intactness and also more simple allowing less room for error 13,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Bone changes of the TMJ condyle were qualitatively measured based on visual evaluation of 9 sections of the TMJ condyle. Cevidanes et al 23,24 suggested a 3 dimensional quantification condylar resorption model technique and Ok et al 11 used superimposition with 6-imaginary sections to assess the longitudinal bone change in TMJ OA. Although both methods are suitable to assess TMJ OA, the method applied in this study was sufficient to highlight the importance of cortical bone intactness and also more simple allowing less room for error 13,25 .…”
Section: Discussionmentioning
confidence: 99%
“…The findings presented in this work reveal that designing imaging biomarkers of TMJ OA need to contemplate the presence of different phenotypic morphology, which was an aspect that our team had investigated before 17 . Our other preliminary studies concentrated in the design of classification methods 18 and were not able to consistently separate among different groups.…”
Section: Discussionmentioning
confidence: 92%
“…58 Zastosowanie obrazowania jest konieczne, ponieważ same kryteria kliniczne stanowią niewystarczające dane do prawidłowego rozpoznania zapalenia stawów sż, ponadto stwierdzono słabe zależności między występowaniem zmian kostnych a klinicznymi objawami ssż w OA, w tym przypadku zastosowanie CBCT zapewnia czytelną wizualizację twardych tkanek ssż. 57,59 Badanie Kothari i wsp. odnośnie profilowania bólu u pacjentów z bólami stawowymi ssż i pacjentów z chorobą zwyrodnieniową stawów wykazały, że w przypadku pierwszej grupy, przy ocenie funkcji somatosensorycznej…”
Section: Choroba Zwyrodnieniowa Stawów (Ang Osteoarthritis -Oa)unclassified